2004
DOI: 10.1159/000079570
|View full text |Cite
|
Sign up to set email alerts
|

Genome architecture studied by nanoscale imaging: analyses among bacterial phyla and their implication to eukaryotic genome folding

Abstract: The proper function of the genome largely depends on the higher order architecture of the chromosome. Our previous application of nanotechnology to the questions regarding the structural basis for such macromolecular dynamics has shown that the higher order architecture of the Escherichia coli genome (nucleoid) is achieved via several steps of DNA folding (Kim et al., 2004). In this study, the hierarchy of genome organization was compared among E. coli, Staphylococcus aureus and Clostridium perfringens. A one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 48 publications
0
31
0
Order By: Relevance
“…The recent development of atomic force microscopy (AFM) [33] has been a breakthrough in the study of nuclear architecture [16,34,35]. The instrumentation and application of AFM have been enormously fruitful due to the development of sharp cantilevers for molecular imaging [36][37][38], cantilever modification techniques for single-molecule force measurement [39][40][41][42][43], and fast-scanning devices for realtime imaging [44][45][46][47][48].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent development of atomic force microscopy (AFM) [33] has been a breakthrough in the study of nuclear architecture [16,34,35]. The instrumentation and application of AFM have been enormously fruitful due to the development of sharp cantilevers for molecular imaging [36][37][38], cantilever modification techniques for single-molecule force measurement [39][40][41][42][43], and fast-scanning devices for realtime imaging [44][45][46][47][48].…”
mentioning
confidence: 99%
“…These lines of evidence suggest that the 30-to 40-nm thin fiber and the 70-to 80-nm granular fiber are the fundamental structural units of eukaryotic chromosomes; these fibers are relatively stable in a wide range of experimental conditions. Recent reports have demonstrated that these hierarchical structures exist in both eukaryotes and prokaryotes [35] and that nascent single-stranded RNAs are part of the 30-80 nm fiber structures [62,63].…”
mentioning
confidence: 99%
“…However, in terms of "structure", biochemical analyses are somewhat limited due to their reliance on inherent indirect detection systems. By contrast, AFM has the potential to visualize such structures directly [12,13]. Genomic DNA interacts with an assortment of proteins and forms a hierarchical higher-order structure called "chromatin".…”
Section: Genome Organizationmentioning
confidence: 99%
“…The current model of the genomic DNA hierarchy includes the step-wise formation of higher-order folding of the genome with different nuclear proteins [12]. However, the folding mechanisms beyond 30 nm fibers are still completely open questions.…”
Section: Genome Organizationmentioning
confidence: 99%
“…Furthermore, they are highly variable depending on growth phase: roughly 70% are replaced from the log to stationary phase in S. aureus. The nucleoid from lysed cells is usually a fibrous structure varying in thickness when observed by the 'on-substrate lysis' method with atomic force microscopy regardless of the growth phase (84), but the physical characteristics of the nucleoid change in response to oxidative stress, where the MrgA protein plays a key role (57,58).…”
Section: Cell Architecture Dynamics: Nucleoidmentioning
confidence: 99%